news - Tkacheva, Marina; Smirnova, Olga; Gutsol, Olga; Dudnev, Alexander; Grigorieva, Anna (project baikal, 2012)
UIA News A Thinking Head and a Nursing Cow The Regular General Meeting of the Members of the Self-Regulatory Organization Independent Partnership “The Baikal Association of Architects and Engineers” of March 23 “BukhArt”: the Beginning of the Second Five-Year Period The VIIth Forum of Architects-Skiers from Siberia and Ural The Second Landscape Conference in Krasnoyarsk “Geo-Decor”, so Simple and Unexpected 254 Years and the 20th Anniversary The Book “Irkutsk Architects” Arkhangelsk Museum of Wooden Architecture «Malye Korely» The Valletta Principles for the Safeguarding and Management of Historic Cities, Towns and Urban Areas Creative Project in Vologda The Nomad 2. Circles and Spirals